2014
DOI: 10.3389/fpsyg.2014.01063
|View full text |Cite
|
Sign up to set email alerts
|

Is the frontal lobe involved in conscious perception?

Abstract: When studying the neural mechanisms underlying conscious perception we should be careful not to misinterpret evidence, and delineate these mechanisms from activity which could reflect the prerequisites or consequences of conscious experiences (Aru et al., 2012; de Graaf et al., 2012). However, at the same time, we need to be careful not to exclude any relevant evidence about the phenomenon. Recently, novel paradigms have attempted to dissociate activity related to conscious perception from activity reflecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…This result led to a flurry of controversy [17,18] in which different types of experiments seemed to differ in whether they showed prefrontal differences in perceptual transitions in a paradigm closely related to binocular rivalry. These results presented serious challenges to the conclusion just described.…”
Section: No-report Paradigm In Binocular Rivalrymentioning
confidence: 99%
See 2 more Smart Citations
“…This result led to a flurry of controversy [17,18] in which different types of experiments seemed to differ in whether they showed prefrontal differences in perceptual transitions in a paradigm closely related to binocular rivalry. These results presented serious challenges to the conclusion just described.…”
Section: No-report Paradigm In Binocular Rivalrymentioning
confidence: 99%
“…These results presented serious challenges to the conclusion just described. In particular, prefrontal reflections of perceptual contents were decoded in a noreport experiment with monkeys using electrophysiological methods (electrodes inserted in cortical regions) that are known to be more sensitive to neural activations than the fMRI used in the result mentioned in the last paragraph [17]. Impressively, these results used monkeys that had not been trained on a discrimination task, ruling out covert decision-making that would have been expected to make a prefrontal difference (personal communication from Theofanis Panagiotaropoulos, the corresponding author of [17].).…”
Section: No-report Paradigm In Binocular Rivalrymentioning
confidence: 99%
See 1 more Smart Citation
“…Its proponents among others have suggested that the neural substrates underlying conscious perception can be traced to a "posterior cortical hot zone", with PFC being primarily critical for processing the behavioral and cognitive consequences of conscious perception (24)(25)(26) like task demands and monitoring, introspection and motor reports, rather than consciousness per se (26)(27)(28)(29). For example, frontal cortex was found to be dramatically more active during motor reports, when blood-oxygen-level-dependent (BOLD) fMRI signal modulation was compared between reported and unreported spontaneous changes in the content of consciousness (27,30,31). Additionally, reduced frontal activation accompanied inconspicuous and unreportable switches in perception, when contrasted against a condition, where perceptual changes were easily discernible (29).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, regarding neuroanatomy, our primary hypothesis is that consciousness is associated with what has traditionally been regarded as "perceptual" regions of the brain, a hypothesis that challenges some accounts of consciousness in which consciousness is associated with executive processes in frontal cortex (e.g., Boly et al 2011;Dehaene & Naccache 2001;Lau 2008;Panagiotaropoulos et al 2012;Safavi et al 2014;Velly et al 2007). Our secondary hypothesis is that olfactory consciousness can be constituted entirely by cortical circuits.…”
Section: Neural Evidence Supports the Sensorium Hypothesismentioning
confidence: 83%